2(3p-1)-3(p-4)=

Simple and best practice solution for 2(3p-1)-3(p-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3p-1)-3(p-4)= equation:


Simplifying
2(3p + -1) + -3(p + -4) = 0

Reorder the terms:
2(-1 + 3p) + -3(p + -4) = 0
(-1 * 2 + 3p * 2) + -3(p + -4) = 0
(-2 + 6p) + -3(p + -4) = 0

Reorder the terms:
-2 + 6p + -3(-4 + p) = 0
-2 + 6p + (-4 * -3 + p * -3) = 0
-2 + 6p + (12 + -3p) = 0

Reorder the terms:
-2 + 12 + 6p + -3p = 0

Combine like terms: -2 + 12 = 10
10 + 6p + -3p = 0

Combine like terms: 6p + -3p = 3p
10 + 3p = 0

Solving
10 + 3p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 3p = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 3p = 0 + -10
3p = 0 + -10

Combine like terms: 0 + -10 = -10
3p = -10

Divide each side by '3'.
p = -3.333333333

Simplifying
p = -3.333333333

See similar equations:

| 78200/(68*46)= | | 6p+10q=400 | | logx^2-1=0 | | (5x^5y^7)^-2/10x^3y^5 | | 56ab/a=0 | | .07(18000-x)+.1x=1590 | | M^4+4m^2-12=0 | | 2a+6b=100 | | 3x-18/9-x= | | 9=3x^2-3x | | sin(2x)+3cos(2x)=0 | | f(-1)=3/(x^5) | | 3x+104=0 | | 5x-4p=27 | | 4x+22=-17+7x | | X-3-5=3 | | 2c+14=6-5 | | 1/5w-3=6/5w | | (9x-y)=0 | | 4x+28=340 | | p+(-2)=6 | | (-3)-3= | | 3x+y=2480 | | v/3=2 | | 5w+5=w-10 | | -116=4x+2(-6x-10) | | 4x-2=-5x+18-2x | | -11x-82=-148 | | 4x-5(-x-2)=9 | | 3=5x+2(-4x-12) | | 382839492818-919383647447= | | -5x-4(x+2)=100 |

Equations solver categories